Tears of salt - Bartolo, Pietro (W.W. Norton & Company, 2018)
Tears of Salt is Dr. Bartolo’s moving account of his life and work set against one of the signal crises of our time. With quiet dignity and an unshakable moral center, he tells unforgettable tales of pain and hope, stories of those who didn’t make it and those who did. Tears of Salt is a lasting work of literature and an intimate portrait of a remarkable man whose inspiring message rings clear: "We can’t and we won’t be governed by our fears."